2012
DOI: 10.1134/s106816201206012x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant diphtheria toxin derivatives: Perspectives of application

Abstract: Diphtheria toxin (DT) is a unique bacterial protein, which selectively kills certain cell populations due to strict functional specialization of domains that allows using this toxin in protein engineering for constructing recombinant derivatives with defined properties. The article covers structural and functional features of DT molecule, both fundamental and practical aspects of recombinant DT derivatives' applications in different fields. In particular, applications of recombinant DT derivatives as unique in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 140 publications
1
3
0
Order By: Relevance
“…At the LB/kanamycin media, the transformed E. coli DH5α and E. coli BL21 were positive for growth. These findings have shown that the progress of the genetic transformation and gene transfer experiences under research has been observed and is also compatible with several previous studies, such as Mohammadi et al [ 21 ], Nascimento et al [ 22 ], and Romaniuk et al [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…At the LB/kanamycin media, the transformed E. coli DH5α and E. coli BL21 were positive for growth. These findings have shown that the progress of the genetic transformation and gene transfer experiences under research has been observed and is also compatible with several previous studies, such as Mohammadi et al [ 21 ], Nascimento et al [ 22 ], and Romaniuk et al [ 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, DTT is better than DTB with regard to antigen load. DTT possesses only one B cell epitope whereas DTB contains several highly immunogenic B cell epitopes in the R domain [ 42 ]. The B cell epitope of DT has been shown to suppress the immune response of certain conjugated haptens by competing DT primed helper T cells [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-toxic DT mutants (cross-reacting materials) have already been applied in animal models to induce effective anti-diphtheria immune response ( 14 ). For example, in our previous study non-toxic recombinant subunit B of DT has been proposed as a safe and effective antigen with a good potential to elicit protective immune response in immunized guinea pigs ( 15 ).…”
Section: Discussionmentioning
confidence: 99%